Investigation of the Biological Function of Fibroblast Activation Protein and its Potential as a Therapeutic Target in Cancer and Diabetes. - Coppage, Andrew. (2017)
Abstract: Fibroblast activation protein is an extracellular post-proline cleaving serine protease belonging to the S9 family of prolyl oligopeptidases. Other members of this family include DPPIV, DPP8, DPP9 and PREP, all of which share the relatively rare ability to cleave peptides after proline residues. This unique specificity suggests possible roles for these proteases in regulation of bioactive peptides as exemplified by DPPIV, which regulates glucose homeostasis through proteolysis of the incretin hormones. DPPIV is now a validated target for the treatment of diabetes, but interest is increasingly being directed at the closely related FAP based on the metabolic syndrome-resistant phenotype of the FAP knockout mouse. This observation implicates FAP as a potential therapeutic target in diabetes. Evidence also exists for FAP as a target in cancer based on observations that FAP is strongly and selectively upregulated on cancer-associated fibroblasts and the demonstrated efficacy of pharmacological inhibitors of FAP in multiple models of cancer, although most of this work has been done with the dipeptide boro-prolines that cross-react with other S9 family members. Work to assess FAP as a drug target in either pathology has thus far been limited by a lack of FAP-specific inhibitors or an FAP-specific substrate to accurately measure inhibition. Fortunately a number of FAP-specific inhibitors and an FAP-specific substrate are now available. Here, we leverage these new tools to show that specific pharmacological inhibition of FAP, DPPIV, FAP+DPPIV, DPP8/9 and PREP are all unable to replicate either the anti-cancer or immune-stimulating effects of the dipeptide boro-prolines. In fact, PREP-specific inhibition appears to accelerate tumor growth. We also show that a FAP-specific inhibitor, although unable to recapitulate many of the aspects of the FAP knockout mouse phenotype, does appear to enhance glucose tolerance, and moreover this effect is additive to that obtained with DPPIV inhibition.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Biochemistry.; Advisor: William Bachovchin.; Committee: Larry Feig, Andrew Bohm, and Brian Schaffhausen.; Keyword: Biochemistry.